Load-Carrying Capacity of Patch-Loaded Stiffened Steel Plate Girders (Journal of University of Babylon for Engineering Sciences, 2019)
This research is aiming to establish an alternative model for determining the ultimate patch load of plate girders with longitudinal stiffener. The proposed model is based on empirical equations and regression analysis and verified with a wide database domain that exists in the literature. A comparison between the results obtained from the proposed model and those obtained from the BS 5400 code specifications is also made in this study. It is found that the proposed model shows a very good agreement with the test results and it is more quite accurate than the BS 5400 code predictions.